Risk factors for anxiety symptoms among Hellenic emergency care nurses - Papathanassoglou, Elizabeth; Stathopoulou, Hariklia; Panagiotopoulou, Fotini; Karanikola, Maria (My University, 2008)
Background: Nurses' burnout syndrome has been studied extensively, worldwide. However, studies investigating the burnout syndrome in nursing staff of Emergency Departments (ED) are limited. Additionally, research evidence associates work stress and burnout with the manifestation of mild psychiatric symptoms. Purpose: The purpose of the present study was to investigate mental health status and burnout levels, as well as the relationship between these two parameters among Hellenic nursing personnel working in Emergency Departments. Methods: A correlational, cross - sectional design was applied. The study sample consisted of 131 randomly selected members of nursing staff who work in general public and private adult's hospitals in Hellas. Burnout levels were measured by the Maslach Burnout Inventory, whilst mental health status was estimated by Hamilton's scale for anxiety states assessment. Results: Moderate levels of emotional exhaustion (23.95+12.96), depersonalization (9.97+7.46) and sense of personal accomplishment (31.99+9.65) were found. Statistically significant moderate positive correlations were detected between burnout indices and anxiety states (tau>0.282 p<0.0001). Additionally, emotional exhaustion was found to be strong predictor of mild psychiatric morbidity among ED nursing personnel (R2=0.308, p<0.0001). Conclusion: The observed moderate levels of burnout indices, as well as the number of participants experiencing depressive mood and sleep disturbances constitute alarming findings. Proposed Implications for practice for the management of burnout and psychiatric morbidities, include continuing professional education programs and nurses psychological empowerment, aimed to the prevention of emotional exhaustion.
Keywords: Nurses; Emergency department; Anxiety; Burnout